Introduction: Striving for social justice and equity in higher education - Okhremtchouk, Irina; Turner, Caroline; Newell, Patrick (Education Policy Analysis Archives, 2021)
Through the introduction of our special issue, Striving for Social Justice and Equity in Higher Education, we aim to add to a continued and much-needed discussion on deeply seated institutional inequities that remain to shape the ways by which education occurs across the higher education landscape. As we present manuscripts included in this issue, our goal is to capture the vast and many layers within higher education encompassing research and discussions on policy and systems that impact administration, leadership, faculty, and student experiences. In our concluding remarks, we stress that even though deeply seated institutional inequities remain, the work of this type must continue as it is part of a broader fight waged for social and racial justice. It is our hope that institutional leaders and policymakers will use the wealth of knowledge shared in this special issue to cultivate nurturing learning environments that include and value the talent and perspectives of those who have been systematically undervalued and marginalized.